Analisis Strategi Pemasaran Pada Kenza Coffee Shop Di Mandalika - Imelda Syahfitri; Lalu M. Furkan; Lalu Edy Herman Mulyono (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this research is to analyze the marketing strategy In Kenza Coffee Shop in Mandalika, Kuta Village, Pujut District, Central Lombok Regency. The research used by researchers in this research is qualitative research with a descriptive approach type. In determining informants as data sources in this study the authors used a purposive sampling technique. The results of the research show that in the marketing strategy carried out by Kenza Coffee Shop the marketing process is divided into several stages, namely starting from segmentation, targeting, positioning, marketing mix. The most effective marketing strategy is to use social media and word of mouth promotion. because visitors will look for a cozie place through social media and from visitors who have visited.